PEMANFAATAN TOGA SEBAGAI MINUMAN SEHAT KELUARGA (HERBAL CELUP) - Anggra Lita Sandra Dewi; Ery Rahmawati; Galuh Kartika Dewi (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
Indonesia has known and used information about medicinal plants based on knowledge and experience that has been passed down from generation to generation which is the hallmark of Indonesian traditional medicine from generation to generation. TOGA (Family Medicinal Plants) is basically a type of garden plant, garden and fields. The TOGA planted by residents includes turmeric, white turmeric, tamarind, and others. Residents of Siwalan Panji village also plant a lot of temulawak which is useful for strengthening the body's immunity, preventing and treating infections, overcoming digestive disorders, maintaining health and liver function, controlling blood sugar levels, and reducing the risk of getting cancer. Seeing the potential and problems that exist in Siwalan Panji Village, Lecturers at STKIP PGRI Sidoarjo held a Community Service program through the use of TOGA as a healthy family drink (HERBAL CELUP). The purpose of this activity is for residents to gain skills in managing TOGA to become an instant herbal drink (Herbal Dip) and this product can later add economic value to the residents of Siwalan Panji village. The location that was used as a place for community service was in Siwalan Panji Village, Buduran District, Sidoarjo Regency with the aim of the service being given to PKK mothers in Siwalan Panji Village, Buduran District, Sidoarjo Regency. The implementation method uses two stages, namely preparation and implementation. In carrying out the activities there are six procedures starting from sorting, production, manufacture, packaging, packaging and marketing. The activity of making herbalup is very easy, only by drying herbal ingredients such as ginger, ginger, turmeric, tamarind, and cinnamon and then packing them using tea bags. KUNJARE is one of the activities of the Siwalanpanji village toga plant business at this time.